2017
DOI: 10.1080/17429145.2017.1414321
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic bacteriumBacillus subtilis(BERA 71) improves salt tolerance in chickpea plants by regulating the plant defense mechanisms

Abstract: Plant growth-promoting endophytic bacteria can stimulate the growth, nutrient acquisition, symbiotic performance and stress tolerance of chickpea plants under saline soil conditions. The aim of this study was to investigate the stress-adaptive mechanisms of chickpea plants mediated by Bacillus subtilis (BERA 71) under saline conditions. Inoculation with BERA 71 enhanced plant biomass and the synthesis of photosynthetic pigments and reduced the levels of reactive oxygen species (ROS) and lipid peroxidation in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
109
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(127 citation statements)
references
References 57 publications
(81 reference statements)
17
109
0
1
Order By: Relevance
“…Treatment with PGPB and/or Si fertilizer elevated the POD activity in plants under saline conditions (Figure 4, Supplementary Table S4). Abd_Allah et al (2018) also reported that salinity stress significantly increased POD activity in chickpea plants, and the level of POD was further elevated in plants inoculated with Bacillus subtilis BERA 71. Similarly, higher activity of POD enzyme in Si treated okra and wheat plants as compared to non-Si treated control plants under salinity stress has been documented by Abbas et al (2015) and Alzahrani et al (2018), respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Treatment with PGPB and/or Si fertilizer elevated the POD activity in plants under saline conditions (Figure 4, Supplementary Table S4). Abd_Allah et al (2018) also reported that salinity stress significantly increased POD activity in chickpea plants, and the level of POD was further elevated in plants inoculated with Bacillus subtilis BERA 71. Similarly, higher activity of POD enzyme in Si treated okra and wheat plants as compared to non-Si treated control plants under salinity stress has been documented by Abbas et al (2015) and Alzahrani et al (2018), respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Deficiency of these nutrients hamper normal activity of photosynthetic pigments, carbohydrate production and yield in maize. Salinity also decline the endogenous levels of phytohormone that results into poor germination (Abd Allah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in the root and vegetative characteristics under salinity conditions when R. officinalis cuttings were treated with IBA may be related to IBA role in increasing lateral root pro duction, inducing adventitious root formation and improving root characteristics and hence increasing uptake of water and nutrients from rooting substrate under the lower saline conditions, leading to enhancing the vegetative growth characteristics (Mostafa, 2002). On the other hand, many studies have showed that inoculation of plants with B. subtilis improves plant growth under salt stress conditions (Abdel-Rahman et al, 2011 andAbd Allah et al, 2017) by influencing IAA production, enhancing the stability of the cell membrane, raising the root vigor of plant and improving photosynthesis under salt stress (Mayak et al, 2004, Mohamed andGomaa, 2012).…”
Section: Root and Shoot Characteristicsmentioning
confidence: 99%
“…The increment in percentages of N, P and K in leaves of R. officinalis rooted cuttings as a response to IBA treatment may be due to the role of IBA in alleviation of adverse effects of salt stress via improving the root system of cuttings, leading to increasing the absorbed amount of N, P and K from the rooting substrate, especially under the lower salinity levels. On the other hand, many studies have showed that inoculation of plants with B. subtilis improves nutrient uptake under salt stress conditions (Abdel-Rahman et al, 2011 andAbd Allah et al, 2017). In addition, PGPR strains such as B. subtilis can produce bacterial exopolysaccharides (EPSs) that bind cations, including Na + (Geddie and Sutherland, 1993), it may be envisaged that increasing the population density of EPS-producing bacteria in the root zone would decrease the content of Na + available for plant uptake and thus help alleviating salt stress in plants growing in saline environments (Ashraf et al, 2004).…”
Section: Minerals Contentmentioning
confidence: 99%
See 1 more Smart Citation